Exploration of hydrogeological conditions of Baotashan sandstone aquifer based on dewatering test - Qiming WEI; Baofeng ZHAO; Zeyuan ZHANG (Meikuang Anquan, 2024)
In order to further explore the hydrogeological conditions of Baotashan sandstone aquifer in Ningdong coalfield and provide basic data for the water disaster prevention and control of the lower coal floor sandstone, the hydrogeological parameters of the aquifer were calculated by dewatering test, and the feasibility of water drainage from aquifer was proved. The results show that: according to the data of dewatering borehole and one observation borehole, two observation boreholes from single borehole dewatering test of Baotashan sandstone, the average permeability coefficient calculated by analytical method is 0.301 m/d and 0.219 m/d, and the average influence radius is 691 m and 914 m, respectively. The average influence radius obtained by graphic method is 697 m, and the unit water inflow is 0.071-0.088 L/(s·m) according to three times of deep drawdown. The hydrogeological parameters obtained by dewater test are large than those obtained by pumping water test. The hydrogeological characteristics of Baotashan sandstone aquifer are weak permeability and water abundance, the water abundance is uneven, and the pressure and water temperature are high. Based on the results of dewater test and the analysis of boundary conditions in the study area, it is found that Baotashan sandstone aquifer has good drainage ability.